New publishing and scientific communication ways: electronic edition, digital educational resources - Cordón García, José António (2016)
The aim of the "New publishing and scientific communication ways: Electronic edition and digital educational resources" track present the problems are those related to digital literacy and the need to establish diagnostics on access and dissemination of information processes, those related to the processing and conservation of the contents, and, finally, those related to the articulation of tools and resources to encourage the development of meta-analysis of contents and specialized journals.